A Systematic Review of Comparing Single-incision Versus Traditional Laparoscopic Right Hemicolectomy For Right Colon Diseases. Issue 6 (December 2019) - Zhao, Guo-Hua; Wang, Haotian; Yu, Hairu; Sun, Jiayi; Zhao, Congxuan; Liu, Yeqiu; Xiong, Jiajia; Chang, Jing; Wang, Mixue; Wang, Wenhui; Ye, Dongman; Zhou, Hongyan; et al.
Abstract : Background: Single-incision laparoscopic right hemicolectomy (SILS) has been promoted in clinic since 2008, but a systematic review of comparing SILS and traditional laparoscopic right hemicolectomy (TLS) with long-term follow-up is rare. Here, in this study, comparison of SILS and TLS with long-term follow-up was evaluated by a meta-analysis method. Methods: All studies about SILS and TLS for right hemicolectomy from 2010 to 2018 were searched from databases including Medline, Embase, Cochrane Library, and Wanfang. Operation index, recovery, and midterm follow-up data were evaluated by fixed-effects models, random-effects models, and Begg test. Results: We collected 22 studies with 2218 patients. SILS groups contained 1038 (46.7%) patients, and 1180 (53.3%) patients were observed in the TLS group. Patients' baseline data were similar in the 2 groups. Compared with TLS, SILS had shorter operation duration [standardized mean difference (SMD): −0.35, 95% confidence interval (CI): −0.61 to −0.08, P <0.001, χ 2 =49.40], shorter hospitalization time (SMD: −0.27, 95% CI: −0.37 to −0.16, P <0.001, χ 2 =9.17), slightly less blood loss (SMD: −0.23, 95% CI: −0.36 to −0.10; P <0.001; χ 2 =5.36), and smaller incision length (SMD: −2.19, 95% CI: −3.66 to −0.71, P <0.001; χ 2 =316.1). No statistical differences were observed in other figures. Conclusion: SILS is more convenient and has better efficacy than TLS and could provide a promising surgical approach for right colon diseases.